COMPARATIVE STUDY OF THE TRADITIONAL VS MODERN TEACHING METHODS - Safarova Mashhura; Aliyeva Shokhsanamkhon (Ustozlar uchun, 2025)
This study explores the comparative effectiveness of traditional and modern teaching methods in enhancing student engagement, knowledge retention, and overall academic performance. With education evolving rapidly due to technological advancements and changing pedagogical approaches, educators face the challenge of selecting methods that best support student success. Traditional methods, characterized by teacher-centered instruction and rote learning, have long been established in educational systems worldwide. In contrast, modern methods, including student-centered and technology-enhanced strategies like flipped classrooms and project-based learning, aim to foster critical thinking, creativity, and active learning.The study employs a mixed-methods approach, utilizing surveys, classroom observations, and interviews with teachers and students from diverse educational settings to examine the strengths, limitations, and impacts of both methods.